Multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization and preparation method thereof
Through in-situ polymerization technology, the multi-element synergy of modified bamboo fibers, phosphorus-containing polymer network flame retardant and N-P modified nanosilica was solved, and the balance between the flame retardant performance and spinning performance of polycapollactam materials was achieved, achieving efficient flame retardant and good heat insulation.
Patent Information
- Application Number
- CN202411951638.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art will lead to changes and degradation of spinning properties when improving the flame retardant properties of polycapollactam materials, making it difficult to find a balance between flame retardant effects and spinning properties, especially under the need to increase the thermal insulation effect of fiber braids.
By using in-situ polymerization, the organic mixture of modified bamboo fibers, phosphorus-containing polymer network flame retardant and N-P modified nanosilica is formed to form a multi-element synergistic flame retardant layer to improve the flame retardant performance of the fibers while maintaining the excellent spinning performance.
It achieves the flame retardant performance of polycapollactam materials without damaging the spinning performance, and imparts good thermal insulation effect to the fiber braid, ensuring the uniformity and effectiveness of the flame retardant performance of the material.
Smart Images

Figure BDA0005215011280000021 
Figure BDA0005215011280000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flame-retardant chemical fiber textiles, and in particular to a multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization and a preparation method thereof. Background Art
[0002] Hydrocarbon polycaprolactam is a linear polyamide produced by the ring-opening polymerization of the monomer caprolactam, and has a repeating unit structure of NH(CH2)5CO. Polycaprolactam (PA6) has excellent tensile strength and wear resistance, is elastic, and is mainly used to make synthetic fibers, and can also be used as engineering plastics. PA6 fiber products are called nylon 6. PA6 fiber has the characteristics of excellent strength, wear resistance, high elastic recovery rate, and easy hygroscopicity. It has always been a fiber material widely used in underwear, home furnishings, and industrial industries. Although pure PA6 fiber has relatively excellent mechanical properties, its flame retardant properties are not ideal. Its limiting oxygen index is only 21-22%, and the molten droplets are serious during combustion, which has a great impact on the safety of actual use.
[0003] In the prior art:
[0004] The patent document with patent number CN103788635 B discloses "a flame-retardant polycaprolactam thermal conductive plastic and its preparation method", which uses aluminum oxide, red phosphorus masterbatch, magnesium hydroxide, antioxidant, lubricant PETS, and anti-dripping agent as auxiliary materials to mix polycaprolactam for blending and extrusion. Although it can effectively improve the flame retardancy of polycaprolactam materials to a certain extent, the blending and addition of these raw materials will also cause changes in the mechanical properties of the final product, and will seriously affect the subsequent spinning performance of polycaprolactam materials. It is difficult to use this blending method to improve the flame retardancy of polycaprolactam in the textile and chemical fiber industry.
[0005] In summary, the existing technology sacrifices the spinning performance of the material while increasing the flame retardant effect. How to effectively flame retard and ensure the spinnability of the material is an urgent problem to be solved. Moreover, with the continuous development of science and technology and the continuous improvement of people's use requirements, the requirements for the additional functions of flame retardant fibers also need to be continuously increased and improved, such as the thermal insulation effect of fiber braids.
[0006] After attempts and research, we have found that the in-situ polymerization method can effectively alleviate the spinnability problem of polycaprolactam materials. The present invention provides a multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization and a preparation method thereof. Summary of the invention
[0007] The purpose of the present invention is to provide a multi-element synergistic flame retardant and thermal insulation fiber prepared by in-situ polymerization and a preparation method thereof. The multi-element synergistic flame retardant and thermal insulation fiber prepared by in-situ polymerization obtained by this method, while satisfying the excellent spinnability of the fiber, adopts different modified substances to achieve multi-element synergistic flame retardancy, and the fiber woven cloth also has good thermal insulation effect.
[0008] To achieve the above object, the present invention is implemented by the following technical solutions:
[0009] A multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization, the flame-retardant heat-insulating fiber comprising the following components in parts by weight:
[0010]
[0011] As a further improvement of this scheme,
[0012] The modified bamboo fiber is a bamboo fiber modified by coating with a dual-element flame-retardant gel;
[0013] The modified bamboo fiber is prepared according to the following steps:
[0014] S1. Pretreatment of bamboo fiber
[0015] The bamboo fibers are placed in an oxidant aqueous solution with a mass fraction of 15-25wt%, and treated in a water bath at 60°C and a rotation speed of 300rpm for 30min, then taken out, and then placed in deionized water for stirring and washing, and then left to stand and drain, and then placed in a 60-70°C oven for drying, and then taken out and stored at room temperature for later use;
[0016] S2. Preparation of dual-element flame-retardant gel
[0017] Take 40-50wt% phosphoric acid aqueous solution, add it into the electric heating reactor, weigh aluminum hydroxide in a ratio of phosphorus to aluminum element of 2.7:1, slowly add it into the phosphoric acid aqueous solution, and stir evenly at a stirring speed of 140-160rpm;
[0018] S3, Gel modification
[0019] The bamboo fibers pretreated in step S1 are placed in a reaction kettle and allowed to react at 100-110° C. for 40-65 minutes. After the reaction is completed, the reaction kettle is opened, the bamboo fibers are taken out, and allowed to stand and drain to obtain modified bamboo fibers.
[0020] As a further improvement of this scheme,
[0021] The oxidant aqueous solution is a phosphorus-based liquid flame retardant, and the phosphorus-based liquid flame retardant is any one or two of TPP and DOPO.
[0022] As a further improvement of this scheme,
[0023] The phosphorus-containing polymer network flame retardant is a phosphorus-containing polysiloxane network flame retardant.
[0024] As a further improvement of this scheme,
[0025] The NP modified nano-silica is prepared according to the following steps:
[0026] S1 UV grafting
[0027] Place the nano-silicon dioxide in a 20g / L NaOH aqueous solution and immerse it at 85°C for 2-4h for chemical etching. After the etching is completed, remove it and dry it in an oven at 60°C for 10min.
[0028] The pretreated nano-silica was immersed in an acetone solution containing grafting monomer and benzophenone for 1 h and then irradiated in a UV box for 15 min;
[0029] After irradiation, the samples were baked at 60 °C for 10 min to remove the residual solvent;
[0030] Finally, the mixture was washed with anhydrous ethanol for 2-3 times, and with deionized water for 2-3 times, and then dried again to obtain ultraviolet grafted nano-silica.
[0031] S2 Surface Modification
[0032] The UV-grafted nano-silica was first immersed in an aqueous solution of methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphorin-5-yl) methyl methyl ester for 15 minutes, then placed in an acetone solution of N-phenylmaleimide for 30 minutes, and then taken out and placed in a forced air oven at 100°C for 20 minutes to obtain NP-modified nano-silica.
[0033] As a further improvement of this scheme,
[0034] The grafting monomer is acrylamide.
[0035] As a further improvement of this scheme,
[0036] In S1, the UV box waveband is 254nm, and the distance between the nano-silicon dioxide and the light source is 15cm.
[0037] A method for preparing the multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization comprises the following preparation steps:
[0038] (1) weighing the raw materials and deionized water in a mass volume ratio of 1 kg: (15-20) L, and mixing and stirring at a stirring speed of 200-650 rpm to prepare a premix;
[0039] (2) placing the premix in a reaction kettle with a jacketed coil, evacuating the air and replacing the air in the kettle with a high-purity inert gas to control the oxygen content in the kettle to less than 0.005%;
[0040] (3) Heating, controlling the pressure at 0.2 MPa-0.4 MPa and the temperature at 230°C-260°C, and reacting in a closed state under pressure for 0.5-1.5 h; then reducing the pressure to 0, and reacting in a vacuum state at a temperature of 215-225°C and a gauge pressure of -0.01 to -0.08 MPa for 0.5-1.0 h, discharging the strip through the discharge valve at the bottom of the reactor, and pelletizing the strip into a pelletizer to obtain a flame-retardant and heat-insulating polycaprolactam, followed by drying and spinning to obtain a flame-retardant and heat-insulating fiber.
[0041] As a further improvement of this scheme,
[0042] Specifically include the following preparation steps:
[0043] (1) weighing caprolactam, modified bamboo fiber, phosphorus-containing polymer network flame retardant, and NP-modified nano-silica in proportion, preparing deionized water in a ratio of 1 kg:17 L of the mass volume ratio of the raw materials to deionized water, and then mixing and stirring at a stirring speed of 200-650 rpm to prepare a premix;
[0044] (2) placing the premix in a reaction kettle with a jacketed coil, evacuating the air and replacing the air in the kettle with a high-purity inert gas to control the oxygen content in the kettle to less than 0.005%;
[0045] (3) Heating, controlling the pressure at 0.2 MPa-0.4 MPa and the temperature at 230°C-260°C, and reacting in a closed state under pressure for 0.5-1.5 h; then reducing the pressure to 0, and reacting in a vacuum state at a temperature of 215-225°C and a gauge pressure of -0.01 to -0.08 MPa for 0.5-1.0 h, discharging the strip through the discharge valve at the bottom of the reactor, and pelletizing the strip in a pelletizer, followed by drying and spinning to obtain a flame-retardant and heat-insulating fiber.
[0046] As a further improvement of this scheme,
[0047] The vacuum reaction time of step (2) is 60 min-80 min, and the high-purity inert gas is high-purity nitrogen containing 99.999% nitrogen or high-purity carbon dioxide containing 99.999% carbon dioxide.
[0048] The present invention discloses a multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization and a preparation method thereof, which has the following beneficial effects:
[0049] 1) The present invention improves the flame retardancy of polycaprolactam materials by organically mixing modified bamboo fibers, phosphorus-containing polymer network flame retardants, and NP-modified nano-silica to form multiple element encirclements of element circles of P-Al, P-Si networks, and "Si-NPN". When combustion occurs, multiple flame retardant layers can be formed to isolate oxygen and heat transfer, thereby achieving a condensed flame retardant effect, and effectively achieving a multi-element synergistic effect to enhance the flame retardant properties of fiber fabrics;
[0050] 2) The fiber prepared by the in-situ polymerization method using caprolactam as a raw material and mixing a flame retardant component can improve the flame retardancy of the material, and at the same time can also ensure the spinning performance of the material to a certain extent, and ensure the uniformity of the flame retardancy of the material;
[0051] 3) The present invention prepares flame-retardant polycaprolactam fiber by mixing caprolactam as a raw material with flame-retardant components and then using an in-situ polymerization method. Such a preparation method can improve the flame retardancy of the material, and at the same time can also ensure the spinning performance of the material to a certain extent, and ensure the uniformity of the flame retardant performance of the material. After testing, the use of multi-stage temperature and pressure control in the reactor can effectively reduce the content of oligomers in the product. According to the GB / T 38138 standard, the relative viscosity is tested, and it is calculated that the viscosity of the flame-retardant and heat-insulating polycaprolactam obtained by pelletizing with a pelletizer of the present invention is between 2.47±0.03, which proves that the flame-retardant and heat-insulating polycaprolactam of the present invention has good spinnability;
[0052] 4) Dendrite-like accumulated gel-like phosphorus-aluminum dual-element gel will form on the surface of bamboo fibers, which is macroscopically manifested as gel coverage of bamboo fibers. Moreover, in the hydrothermal reaction of bamboo fibers, phosphorus-aluminum crystals can not only form a coating layer on the surface of bamboo fibers, but also form a coating layer with nano-scale sheets on the inner wall of the cell cavity of bamboo fibers, and bond with the fibers, which is beneficial to the improvement of mechanical properties. In terms of flame retardancy, the surface of bamboo fibers contains a large number of polar hydroxyl and phenolic hydroxyl functional groups, which makes it difficult for the heat generated when bamboo fibers burn to accumulate, which makes it difficult for them to burn continuously. In addition, the phosphorus-aluminum crystal structure layer can form a cracked carbon layer through Al-O and the dehydration endothermic effect during the combustion process to play a flame retardant effect. The pyrolysis process produces acid for dehydration into carbon, which effectively improves the residual carbon rate and thermal stability of the prepared modified bamboo fibers.
[0053] 5) The present invention can form multiple element encirclements of P-Al, P-Si network, and "Si-NPN" element circles through the organic mixing of modified bamboo fiber, phosphorus-containing polymer network flame retardant, and NP-modified nano-silica. When burning occurs, multiple flame retardant layers can be formed to isolate oxygen and heat transfer, thereby achieving a condensed flame retardant effect. Moreover, by mixing caprolactam as a raw material with flame retardant components and preparing the fiber by in-situ polymerization, the flame retardancy of the material can be improved, and the spinning performance of the material can be guaranteed to a certain extent, and the uniformity of the flame retardant performance of the material can be guaranteed. DETAILED DESCRIPTION
[0054] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described below in conjunction with embodiments:
[0055] The present invention prepares flame-retardant polycaprolactam fiber by mixing caprolactam as raw material with flame-retardant component material and then using in-situ polymerization method. Such preparation method can improve the flame retardancy of the material, and at the same time can also ensure the spinning performance of the material to a certain extent, and ensure the uniformity of the flame retardant performance of the material. After testing, the use of multi-stage temperature and pressure control in the reactor can effectively reduce the content of oligomers in the product. According to the GB / T 38138 standard, the relative viscosity is tested, and it is calculated that the viscosity of the flame-retardant and heat-insulating polycaprolactam obtained by pelletizing with a pelletizer of the present invention is between 2.47±0.03, which proves that the flame-retardant and heat-insulating polycaprolactam of the present invention has good spinnability.
[0056] Furthermore, during the in-situ polymerization of PA6 materials:
[0057] Bamboo fiber was used as one of the performance modification raw materials. The bamboo fiber was short-cut bamboo fiber purchased from Xineng Textile Technology Co., Ltd. The model is 1.5D white bamboo charcoal bamboo fiber.
[0058] In order to allow the dual-element flame-retardant gel to penetrate into the interior of the chopped bamboo fibers as much as possible, we carried out delignification pretreatment on the chopped bamboo fibers. Specifically, the bamboo fibers were placed in an aqueous solution of an oxidant with a mass fraction of 15wt%, and a multi-head magnetic stirrer was used to control the temperature at 60°C in a water bath and the speed at 300rpm for 30 minutes. Then, they were taken out and placed in deionized water for stirring and washing. After being taken out, they were allowed to stand and drain, and then placed in a 60°C oven for drying, and then taken out and stored at room temperature for later use.
[0059] Subsequently, the bamboo fiber modified with dual-element flame retardant gel was prepared by taking a 45wt% phosphoric acid aqueous solution, adding it to an electric heating reactor, weighing aluminum hydroxide according to a phosphorus-aluminum molar ratio of 2.7:1, and slowly adding it to the phosphoric acid aqueous solution, and stirring it evenly at a stirring speed of 150rpm. Finally, the pretreated bamboo fiber was placed in the reactor and allowed to react at 110°C for 50 minutes. After the reaction was completed, the reactor was opened, the bamboo fiber was taken out, and it was allowed to stand and drain to obtain the modified bamboo fiber.
[0060] Generally, the dual-element flame-retardant gel is stirred at a speed of 150-300rpm in an electric heating reactor, and 45% phosphoric acid solution is slowly added to keep the stirrer rotating at a constant speed so that the solution in the bottle releases heat completely. Keep the stirrer rotating at a constant speed, heat up the magnetic stirring heater, so that the temperature of the solution in the beaker rises to 85-90°C, slowly add aluminum hydroxide to the solution, and stir until the exothermic reaction is completed. After the solution temperature stabilizes, the stirring speed is increased to 300-450rpm, the solution temperature rises to 90-120°C, the reaction time is controlled, and after the reaction to a constant temperature, a transparent and viscous inorganic glue solution can be obtained. The glue solution is then cooled to room temperature to obtain the P-Al dual-element flame-retardant gel. The P-Al dual-element flame-retardant gel can be directly configured into an aqueous solution for fiber impregnation treatment, but this will cause the dual-element flame-retardant gel to only adhere to the fiber surface, limiting the flame retardant effect. The bamboo fibers are placed in a reactor at the same time and allowed to react at 100-110°C for 40-65 minutes. One purpose is to make the gel more wettable, not only adhering to the fiber surface but also penetrating into the interior of the bamboo fibers, thereby better playing a flame retardant role; the second is to utilize the structural characteristics of the bamboo fibers to provide more phosphorus source and aluminum source reaction space, as well as crystal growth sites.
[0061] Wherein, the oxidant aqueous solution is a phosphorus-based liquid flame retardant aqueous solution, and the present invention is preferably TPP. The phosphorus-based liquid flame retardant aqueous solution has strong oxidizing properties and has two functions in the modified bamboo fiber: one is that it can effectively remove lignin, thereby increasing the reaction space between the phosphorus source and the aluminum source; the other is that after surface treatment, the phosphorus element attached to the surface of the bamboo fiber can reduce the amount of phosphorus source used in the subsequent dual-element flame retardant gel. According to actual output calculation, the molar ratio of phosphorus and aluminum elements prepared in the dual-element flame retardant gel should be 3:1. After many tests and effect comparisons, we use a phosphorus-aluminum molar ratio of 2.7:1 to weigh aluminum hydroxide to meet the use requirements. The bamboo fiber after swelling treatment with the peroxide aqueous solution allows the phosphorus-aluminum inorganic matter to penetrate into the bamboo fiber as much as possible, and completes the hydrothermal in-situ reaction between the fibers.
[0062] Furthermore, in the synthesis reactor, due to the change in temperature rise, the pressure generated in the reactor will increase with the increase of reaction temperature, thereby affecting the nucleation and growth of the material crystal. In order to make phosphoric acid and aluminum hydroxide crystals grow and nucleate into inorganic colloids, the temperature needs to be controlled above 100°C. As the temperature rises, phosphorus-aluminum crystals are gradually nucleated on the inner surface of bamboo fibers, and in the reactor environment, a dendrite-like accumulated gel-state phosphorus-aluminum dual-element gel will be formed on the surface of bamboo fibers, which is macroscopically manifested as gel coverage of bamboo fibers. Moreover, in the hydrothermal reaction of bamboo fibers, phosphorus-aluminum crystals can not only form a coating layer on the surface of bamboo fibers, but also form a coating layer with nano-scale sheets on the inner wall of the cell cavity of bamboo fibers, and bond with the fibers, which is conducive to the improvement of mechanical properties. In terms of flame retardancy, the surface of bamboo fibers contains a large number of polar hydroxyl and phenolic hydroxyl functional groups, which makes it difficult to accumulate the heat generated when bamboo fibers burn, which makes it difficult to continue to burn. In addition, the phosphorus-aluminum crystal structure layer can form a cracked carbon layer through Al-O and the dehydration endothermic effect during the combustion process to achieve a flame retardant effect. The pyrolysis process produces acid for dehydration into carbon, which effectively improves the residual carbon rate and thermal stability of the prepared modified bamboo fiber.
[0063] Furthermore, the phosphorus-containing polymer network flame retardant is a phosphorus-containing polysiloxane network flame retardant. Furthermore, the preparation method of the phosphorus-containing polysiloxane network flame retardant is as follows:
[0064] Synthetic flame retardant monomers:
[0065] Take diphenyl phosphite in a single-necked flask, add 1-butenyl (3,3-dimethyl) triethoxysilane, the molar ratio of diphenyl phosphite to 1-butenyl (3,3-dimethyl) triethoxysilane is 5:6, then add 1% initiator AIBN (relative to 1-butenyl (3,3-dimethyl) triethoxysilane), and then add dichloromethane, the volume of dichloromethane is 1.5 times the volume of the raw materials after mixing. Under N2 protection, react at 80°C for 24 hours, and finally remove the solvent by rotary evaporation to obtain a flame retardant monomer.
[0066] Polymer network building synthesis:
[0067] The phosphorus-containing polymer network flame retardant is synthesized by hydrolysis-condensation reaction, specifically, a synthesized flame retardant monomer is taken, a certain proportion of alcohol-water mixed liquid is added, wherein the ratio of water to ethanol is 2:1, and a precursor solution with a concentration of 25% is prepared; then, under the protection of N2, the solution is reacted at 80°C for 18h, the solution is allowed to stand and then washed with water for 2-3 times, and dried at 45°C to obtain the phosphorus-containing polymer network flame retardant.
[0068] The phosphorus-containing polymer network flame retardant is a phosphorus-containing polysiloxane network flame retardant. According to the chemical substances involved in the reaction, the phosphorus-hydrogen bond and the carbon-carbon double bond addition reaction are used to prepare the phosphorus-containing siloxane monomer, and then the network polymer form is formed through the hydrolysis-condensation reaction. Moreover, according to the reaction size dimension, the phosphorus-containing polymer network flame retardant does not affect the fabric interweaving structure at all. In this way, the network polymer form is evenly distributed in the PA6 fiber. When encountering external combustion, the P-Si network can cross-link with C during combustion to form a carbon layer, which can isolate oxygen and heat transfer, thereby enhancing the cohesive flame retardant effect and thermal insulation effect of the material.
[0069] Furthermore, the preparation method of NP-modified nano-silica comprises the following steps:
[0070] UV grafting: Place the nano-silica in a 20g / L NaOH aqueous solution, immerse it at 85°C for 2-4h for chemical etching, and then take it out and dry it in a 60°C oven for 1 minute; immerse the pretreated nano-silica in an acetone solution containing grafting monomers and photoinitiator benzophenone for 1h, and irradiate it in a UV box for 15min; after irradiation, bake it at 60°C for 10min to remove residual solvent; finally, wash it with anhydrous ethanol 2-3 times, wash it with deionized water 2-3 times, and then dry it again to remove unreacted monomers to obtain UV-grafted nano-silica.
[0071] Surface modification: The UV-grafted nano-silica was first immersed in an aqueous solution of methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphorin-5-yl) methyl ester for 15 minutes, and then placed in an acetone solution of N-phenylmaleimide for 30 minutes. After being taken out, it was placed in a forced air oven and dried at 100°C for 20 minutes to obtain NP-modified nano-silica.
[0072] The preparation of NP-modified nano-silica is to firstly perform alkali etching, and then irradiate with ultraviolet light to excite the photoinitiator benzophenone, and initiate the copolymerization between the grafted monomers in the acetone solvent, thereby generating a grafted polymer chain on the surface of the nano-silica. In the further surface modification process, through the soaking process, the methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphoric acid-hexa-5-yl) methyl methyl ester containing the P element is attached to the surface of the nanoparticles, and the further treatment and attachment of N-phenylmaleimide can make the nano-silica particles form an elemental ring layer of "Si-NPN" from the inside to the outside, which has a good heat insulation effect. Moreover, the methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphoric acid-hexa-5-yl) methyl methyl ester will produce free radicals when heated, which can capture the hydrogen free radicals produced by the thermal decomposition of bamboo fibers in the fabric, and can inhibit the combustion reaction. Furthermore, the grafted monomer and methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphorin-5-yl) methyl methyl ester can form a NP synergistic effect, forming a phosphoramide structure during combustion, further improving the flame retardant properties of the fiber fabric; N-phenylmaleimide promotes the carbonization of the fabric and inhibits the thermal decomposition of the fabric.
[0073] Performance Testing
[0074] Main physical properties test of textiles
[0075] 1. Flame retardant performance test:
[0076] (1) Limiting oxygen index (LOI) test:
[0077] The flame-retardant and heat-insulating polycaprolactam prepared in situ in each group was dried and then injection molded into standard specimens with a specimen size of 100 mm×10 mm×3.2 mm. The specimens were subjected to a limiting oxygen index test according to GB / T 2406.2.
[0078] (2) Vertical burning (UL94) test
[0079] Each group of flame-retardant polycaprolactam composite materials was dried and injection molded into standard specimens with a specimen size of 125mm×12.5mm×3.2mm. The specimens were subjected to a vertical combustion test according to GB / T 2408, where t1 is the afterflame time of the first ignition; t2 is the afterflame time of the second ignition;
[0080] 2. Thermal insulation performance test:
[0081] According to GB / T 41560-2022 "Determination of heat shielding properties of textiles", the performance of textiles in suppressing temperature rise by shielding light radiation is measured. Laboratories generally use xenon lamps to simulate sunlight for testing, and use heat shielding rate and maximum temperature as evaluation criteria: the greater the heat shielding rate, the more light radiation the sample shields; the lower the maximum temperature, the lower the perceived temperature when the sample is worn.
[0082] 3. Mechanical properties testing:
[0083] The flame retardant and heat insulating fibers of Examples 1-3 and the PA6 fiber prepared in the comparative example were drawn by a drawing machine, the drawing speed was 1000 m / min, the temperature of the hot roller of the traction machine was 58°C, and the drawing multiple was 3.6. The single yarn strength tester YG020B was used for testing according to GB / T 14344 standard, the drawing speed was 350 mm / min, the clamping distance was 500 mm, the pre-tension was 5 cN, and 5 groups of valid data were obtained for each group of samples, and the average value was taken to test the breaking strength and breaking elongation.
[0084] Examples 1-3
[0085] A multi-element synergistic flame-retardant heat-insulating fiber prepared by in-situ polymerization, wherein the flame-retardant heat-insulating fiber comprises the following raw materials in parts by weight:
[0086] Caprolactam, modified bamboo fiber, phosphorus-containing polymer network flame retardant, NP-modified nano-silica.
[0087] In Examples 1-3, raw materials such as caprolactam were weighed according to the proportions shown in Table 1.
[0088] The in-situ preparation method of the flame retardant heat-insulating fiber comprises the following steps:
[0089] (1) weighing the raw materials and deionized water in a mass volume ratio of 1 kg: (15-20) L, and mixing and stirring at a stirring speed of 200-650 rpm to prepare a premix;
[0090] (2) placing the premix in a reaction kettle with a jacketed coil, evacuating the air and replacing the air in the kettle with a high-purity inert gas to control the oxygen content in the kettle to less than 0.005%;
[0091] (3) Heating, controlling the pressure at 0.2 MPa-0.4 MPa and the temperature at 230°C-260°C, and reacting in a closed state under pressure for 0.5-1.5 h; then reducing the pressure to 0, and reacting in a vacuum state at a temperature of 215-225°C and a gauge pressure of -0.01 to -0.08 MPa for 0.5-1.0 h, discharging the strip through the discharge valve at the bottom of the reactor, and pelletizing the strip in a pelletizer, followed by drying and spinning to obtain a flame-retardant and heat-insulating fiber.
[0092] Preferably, a spinning machine (VC406B) is used for spinning, a drawing machine (VC443A) is used for stretching, and the spinneret specifications used are: 0.3mm×36f, the spinning speed is 700m / min, and the flame retardant and heat insulating fibers obtained after spinning are stretched by a drawing machine, the stretching speed is 1000m / min, the temperature of the hot roller of the traction machine is 58°C, and the stretching multiple is 3.6.
[0093] Further, in Examples 1-3, the mass volume ratio of the raw materials and deionized water in step (1) is 1 kg: 17 L, and then the mixture is mixed and stirred at a stirring speed of 450 rpm to obtain a premix. Further, the vacuum reaction time in step (2) is 70 minutes, and the high-purity inert gas is high-purity nitrogen with a nitrogen content of 99.999%.
[0094] Furthermore, in step (3), the temperature is raised, the pressure is controlled at 0.2Mpa-0.4Mpa, the temperature is 245°C, and the reaction is carried out in a closed state under pressure for 0.7h; then the pressure is released to 0, and the reaction is carried out in a vacuum state at a temperature of 220°C and a gauge pressure of -0.01 to -0.08Mpa for 0.8h, and the strip is discharged through the discharge valve at the bottom of the reactor, and the strip is fed into a pelletizer for pelletizing, followed by drying and spinning to obtain flame-retardant and heat-insulating fibers.
[0095] Furthermore, the modified bamboo fiber is a bamboo fiber coated with a dual-element flame-retardant gel, and the preparation method of the modified bamboo fiber comprises the following steps:
[0096] S1. Pretreatment of bamboo fiber
[0097] The bamboo fibers were placed in an aqueous solution of an oxidant with a mass fraction of 15 wt%, and treated in a water bath at 60°C and a rotation speed of 300 rpm for 30 min. The fibers were then taken out and placed in deionized water for stirring and washing. The fibers were then left to stand and drained, dried in an oven at 65°C, and stored at room temperature for later use.
[0098] S2. Preparation of dual-element flame-retardant gel
[0099] Take 45wt% phosphoric acid aqueous solution, add it into the electric heating reactor, weigh aluminum hydroxide in a ratio of phosphorus to aluminum element of 2.7:1, slowly add it into the phosphoric acid aqueous solution, and stir it evenly at a stirring speed of 150rpm;
[0100] S3, Gel modification
[0101] The bamboo fibers pretreated in step S1 were placed in a reaction kettle and allowed to react at 105° C. for 50 minutes. After the reaction was completed, the reaction kettle was opened, the bamboo fibers were taken out, and allowed to stand and drain to obtain modified bamboo fibers.
[0102] Comparative Example 1
[0103] Different from Example 1, the raw materials are weighed according to the various ratios in Table 1, and the modified bamboo fiber is directly obtained by double dipping and double rolling treatment of the dual-element flame retardant gel liquid, wherein the rolling pressure is 0.2 MPa and the speed is 25 m / min. After drying, it is added to the caprolactam system according to the proportions in Table 1.
[0104] The details are as follows: prepare bamboo fibers, immerse the bamboo fibers in a 15% phosphoric acid aqueous solution, heat in a water bath at 60°C and stir at 300rpm to remove non-fibrous components such as pulp and lipid wax on the surface of the bamboo fibers, and dry the bamboo fibers in the shade for later use to obtain pretreated bamboo fibers.
[0105] Take 45wt% phosphoric acid aqueous solution, add it to the electric heating reactor, weigh aluminum hydroxide according to the ratio of phosphorus to aluminum element molar ratio of 2.7:1, slowly add it to the phosphoric acid aqueous solution, and stir evenly at a stirring speed of 150rpm; at room temperature, prepare a beaker containing distilled water, stir at a speed of 150-300rpm, slowly add 45% phosphoric acid solution to keep the stirrer rotating at a constant speed, so that the solution in the bottle releases heat completely. Keep the stirrer rotating at a constant speed, heat up the magnetic stirring heater, so that the temperature of the solution in the beaker rises to 85-90℃, slowly add aluminum hydroxide to the solution, and stir until the exothermic reaction is completed. After the solution temperature stabilizes, the stirring speed is increased to 300-450rpm, the solution temperature rises to 90-120℃, the reaction time is controlled, and after the reaction to the constant temperature, a transparent and viscous inorganic glue solution can be obtained. Then the glue solution is cooled to room temperature to obtain a dual-element flame-retardant gel.
[0106] Subsequently, the dual-element flame retardant gel was prepared into a solution with a bath ratio of 1:20, and the bamboo fiber was pretreated by a two-immersion and two-rolling immersion treatment. The treatment was carried out at room temperature and normal pressure, and the obtained test pieces were placed in a drying oven and dried at 65°C.
[0107] For other processes, refer to Example 1.
[0108] Comparative Examples 2-7
[0109] The difference from Example 1 is that the raw materials are weighed according to the ratios in Table 1, and the other processes refer to Example 1.
[0110] The samples of Examples 1-3 and Comparative Examples 1-7 were prepared according to different performance test standards and subjected to relevant performance tests. The test results are shown in Table 1.
[0111] Table 1 Material ratio and test results analysis table
[0112]
[0113] From the comparative analysis of the test results of Examples 1 to 3 and Comparative Examples 1 to 7 in Table 1 above, it can be seen that the modified bamboo fiber, the phosphorus-containing polymer network flame retardant, and the NP-modified nano-silica can form the NP synergistic effect of the elemental circles of P-Al, P-Si networks, and "Si-NPN", which can effectively play a multi-element synergistic role in enhancing the flame retardant properties of the fiber fabric, and the phosphorus-containing polymer network flame retardant and the NP-modified nano-silica also have the function of synergistic heat insulation.
[0114] Furthermore, in Comparative Example 1, since the dual-element flame retardant gel and the bamboo fiber did not undergo a synchronous hydrothermal in-situ reaction, its effect remained on the fiber surface, so that the flame retardant effect was limited.
[0115] In Comparative Examples 5-7, due to the single added ingredients and the low usage of phosphorus-containing polymer network flame retardant and NP-modified nano-silica, the flame retardancy and mechanical properties of PA6 fiber are relatively weak. NP-modified nano-silica also has a significant synergistic effect on mechanical strength.
[0116] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A multi-element synergistic flame-retardant thermal insulation fiber prepared by in-situ polymerization, characterized in that: The flame retardant heat insulating fiber comprises the following components in parts by weight: 100 parts of caprolactam; 12-15 parts of modified bamboo fiber; 4.5-6.5 parts of phosphorus-containing polymer network flame retardant; NP modified nano-silica 1.5-3.5 parts.
2. The multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 1, characterized in that: The modified bamboo fiber is a bamboo fiber modified by coating with a dual-element flame-retardant gel; The modified bamboo fiber is prepared according to the following steps: S1. Pretreatment of bamboo fiber The bamboo fibers are placed in an oxidant aqueous solution with a mass fraction of 15-25wt%, and treated in a water bath at 60°C and a rotation speed of 300rpm for 30min, then taken out, and then placed in deionized water for stirring and washing, and then left to stand and drain, and then placed in a 60-70°C oven for drying, and then taken out and stored at room temperature for later use; S2. Preparation of dual-element flame-retardant gel Take 40-50wt% phosphoric acid aqueous solution, add it into the electric heating reactor, weigh aluminum hydroxide in a ratio of phosphorus to aluminum element of 2.7:1, slowly add it into the phosphoric acid aqueous solution, and stir evenly at a stirring speed of 140-160rpm; S3, Gel modification The bamboo fibers pretreated in step S1 are placed in a reaction kettle and allowed to react at 100-110° C. for 40-65 minutes. After the reaction is completed, the reaction kettle is opened, the bamboo fibers are taken out, and allowed to stand and drain to obtain modified bamboo fibers.
3. The multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 2, characterized in that: The oxidant aqueous solution is a phosphorus-based liquid flame retardant, and the phosphorus-based liquid flame retardant is any one or two of TPP and DOPO.
4. The multi-element synergistic flame-retardant thermal insulation fiber prepared by in-situ polymerization according to any one of claims 1 to 3, characterized in that: The phosphorus-containing polymer network flame retardant is a phosphorus-containing polysiloxane network flame retardant.
5. The multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 1, characterized in that: The NP modified nano-silica is prepared according to the following steps: S1 UV grafting Place the nano-silicon dioxide in a 20g / L NaOH aqueous solution and immerse it at 85°C for 2-4h for chemical etching. After the etching is completed, remove it and dry it in an oven at 60°C for 10min. The pretreated nano-silica was immersed in an acetone solution containing grafting monomer and benzophenone for 1 h and then irradiated in a UV box for 15 min; After irradiation, the samples were baked at 60 °C for 10 min to remove the residual solvent; Finally, the mixture was washed with anhydrous ethanol for 2-3 times, and with deionized water for 2-3 times, and then dried again to obtain ultraviolet grafted nano-silica. S2 Surface Modification The UV-grafted nano-silica was first immersed in an aqueous solution of methylphosphonic acid (5-ethyl-2-methyl-2-oxo-1,3,2-dioxaphosphorin-5-yl) methyl methyl ester for 15 minutes, then placed in an acetone solution of N-phenylmaleimide for 30 minutes, and then taken out and placed in a forced air oven at 100°C for 20 minutes to obtain NP-modified nano-silica.
6. The multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 5, characterized in that: The grafting monomer is acrylamide.
7. The multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 5, characterized in that: In S1, the UV box waveband is 254nm, and the distance between the nano-silicon dioxide and the light source is 15cm.
8. A method for preparing the multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: (1) weighing the raw materials and deionized water in a mass volume ratio of 1 kg: (15-20) L, and mixing and stirring at a stirring speed of 200-650 rpm to prepare a premix; (2) placing the premix in a reaction kettle with a jacketed coil, evacuating the air and replacing the air in the kettle with a high-purity inert gas to control the oxygen content in the kettle to less than 0.005%; (3) Heating, controlling the pressure at 0.2 MPa-0.4 MPa and the temperature at 230°C-260°C, and reacting in a closed state under pressure for 0.5-1.5 h; then reducing the pressure to 0, and reacting in a vacuum state at a temperature of 215-225°C and a gauge pressure of -0.01 to -0.08 MPa for 0.5-1.0 h, discharging the strip through the discharge valve at the bottom of the reactor, and pelletizing the strip into a pelletizer to obtain a flame-retardant and heat-insulating polycaprolactam, followed by drying and spinning to obtain a flame-retardant and heat-insulating fiber.
9. The method for preparing the multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 8, characterized in that: Specifically include the following preparation steps: (1) weighing caprolactam, modified bamboo fiber, phosphorus-containing polymer network flame retardant, and NP-modified nano-silica in proportion, preparing deionized water in a ratio of 1 kg:17 L of the mass volume ratio of the raw materials to deionized water, and then mixing and stirring at a stirring speed of 200-650 rpm to prepare a premix; (2) placing the premix in a reaction kettle with a jacketed coil, evacuating the air and replacing the air in the kettle with a high-purity inert gas to control the oxygen content in the kettle to less than 0.005%; (3) Heating, controlling the pressure at 0.2 MPa-0.4 MPa and the temperature at 230°C-260°C, and reacting in a closed state under pressure for 0.5-1.5 h; then reducing the pressure to 0, and reacting in a vacuum state at a temperature of 215-225°C and a gauge pressure of -0.01 to -0.08 MPa for 0.5-1.0 h, discharging the strip through the discharge valve at the bottom of the reactor, and pelletizing the strip in a pelletizer, followed by drying and spinning to obtain a flame-retardant and heat-insulating fiber.
10. The method for preparing the multi-element synergistic flame-retardant and heat-insulating fiber prepared by in-situ polymerization according to claim 9, characterized in that: The vacuum reaction time of step (2) is 60 min-80 min, and the high-purity inert gas is high-purity nitrogen containing 99.999% nitrogen or high-purity carbon dioxide containing 99.999% carbon dioxide.
Citation Information
Patent Citations
A flame-retardant polycaprolactam heat-conducting plastic and its preparation method
CN103788635B